Antidiabetic Activity of Pterospermum acerifolium Flowers and Glucose Uptake Potential of Bioactive Fraction in L6 Muscle Cell Lines with Its HPLC Fingerprint. (21st October 2014) - Paramaguru, Rathinavelusamy; Mazumder, Papiya Mitra; Sasmal, Dinakar; Jayaprakash, Venkatesan
Abstract : The present study was designed to estimate the detailed antidiabetic activity of Pterospermum acerifolium (L.) Willd flowers. In vitro alpha amylase inhibition study was carried out on 50% ethanol extract of flowers (PAFEE) and its various fractions. The active ethyl acetate fraction (PAFEF) was subfractionated into three subfractions (PAFE1, PAFE2, and PAFE3) and subjected to acute toxicity studies followed by antidiabetic screening in vivo by streptozotocin-nicotinamide induced type II diabetes. Diabetic animals treated with PAFE2 (30 mg/kg) reduced the levels of fasting blood glucose, significantly (P < 0.001 ) compared to that of diabetic control animals. Histological studies on drug treated groups did not show remarkable positive changes in β -cells. PAFE2 showed 32.6 ± 1.93 % glucose uptake over control and, in the presence of PI3K inhibitor wortmannin, declined to 13.7 ± 2.51 %. HPLC analysis of PAFE2 reveals the presence of quercetin and apigenin as major constituents and both are inhibiting the glycogen phosphorylase enzyme in molecular modelling studies. The study evidenced strongly that the probable glucose lowering mechanism of action of active subfraction PAFE2 is by increasing the glucose uptake in peripheral tissues and by inhibition of gluconeogenesis.